Biocontrol potential of a novel broad-spectrum antifungal strain Bacillus velezensis Shannan.BV80-12 isolated from the Tibetan Plateau - Yali Tan; Feiyan Dong; Rong Wang; Xiao Li; Jialan Zhang; Tong Gu; Li Li; Mengxiang Gao (Biological Control, 2025)
Plant diseases caused by pathogenic fungi are major contributors to global crop loss. Although chemical fungicides are effective for disease control, concerns regarding their adverse effects on human health and the environment have driven interest in sustainable alternatives. Beneficial microorganism-based biological controls have attracted considerable attention in this context. In this study, a novel bacterial strain, Bacillus velezensis Shannan.BV80-12, was isolated from the high-altitude Tibetan Plateau. The strain demonstrated significant inhibitory effects against 21 plant pathogenic fungi across 12 genera, showing inhibition rates between 61.9% and 97.5% in dual-culture assays and between 40.2% and 89.0% in poison agar assays with 2% cell-free supernatant. It also effectively controlled fungal plant diseases in detached leaf assays. Genome sequencing and analysis revealed the genetic basis for its biocontrol efficacy, including 19 biosynthetic gene clusters responsible for secondary metabolites and 23 glycoside hydrolase genes involved in degrading phytopathogen cell walls. UPLC-MS analysis of cell-free supernatants identified six distinct families of antimicrobial metabolites: fengycins (C14–C17), surfactins (C12–C16), iturins (C14–C16), bacillibactin, plantazolicin and bacilysin, suggesting that strain Shannan.BV80-12 possesses the capability to co-produce a variety of bioactive metabolites that synergistically contribute to its strong antimicrobial effects. Genome annotation and comparative genomics further revealed multiple genes associated with bacteria-plant interactions that can enhance plant health and resistance to pathogens, as well as genes crucial for adaptation to harsh environments, which may contribute to the stability and efficacy of the strain in controlling phytopathogens under adverse conditions. These findings elucidate the biocontrol mechanisms of B. velezensis strain Shannan.BV80-12 and support its potential application as a broad-spectrum biocontrol agent against phytopathogenic fungi in sustainable agriculture.